Обучение в школах Ярославля в годы Великой Отечественной войны (по материалам ярославских архивов и музеев) - Страхова Н. В. (Великая Отечественная война в истории народов Поволжья, 2024)
the article examines the features of the organization of education for schoolchildren in the city of Yaroslavl during the Great Patriotic War. The sources used were materials from the municipal archive of the city of Yaroslavl and the catalog of the exhibition of the Museum of the History of the City of Yaroslavl named after V.G. Izvekov «Mood – Victory». The author paid special attention to the state of the material base of schools and the organization of the educational process during the war years.
Keywords: обучение; Великая Отечественная война; школа; training; school; The Great Patriotic War; тыловой город; материальная база; rear city; material base